Evidence of Genomic Diversification in a Natural Symbiotic Population Within Its Host - Bongrand, Clotilde; Koch, Eric; Mende, Daniel; Romano, Anna; Lawhorn, Susannah; McFall-Ngai, Margaret; DeLong, Edward F.; Ruby, Edward G. (Frontiers in Microbiology, 2022)
Planktonic cells of the luminous marine bacterium Vibrio fischeri establish themselves in the light-emitting organ of each generation of newly hatched Euprymna scolopes bobtail squid. A symbiont population is maintained within the 6 separated crypts of the organ for the ~9-month life of the host. In the wild, the initial colonization step is typically accomplished by a handful of planktonic V. fischeri cells, leading to a species-specific, but often multi-strain, symbiont population. Within a few hours, the inoculating cells proliferate within the organ’s individual crypts, after which there is evidently no supernumerary colonization. Nevertheless, every day at dawn, the majority of the symbionts is expelled, and the regrowth of the remaining ~5% of cells provides a daily opportunity for the population to evolve and diverge, thereby increasing its genomic diversity. To begin to understand the extent of this diversification, we characterized the light-organ population of an adult animal. First, we used 16S sequencing to determine that species in the V. fischeri clade were essentially the only ones detectable within a field-caught E. scolopes. Efforts to colonize the host with a minor species that appeared to be identified, V. litoralis, revealed that, although some cells could be imaged within the organ, they were <0.1% of the typical V. fischeri population, and did not persist. Next, we determined the genome sequences of seventy-two isolates from one side of the organ. While all these isolates were associated with one of three clusters of V. fischeri strains, there was considerable genomic diversity within this natural symbiotic population. Comparative analyses revealed a significant difference in both the number and the presence/absence of genes within each cluster; in contrast, there was little accumulation of single-nucleotide polymorphisms. These data suggest that, in nature, the light organ is colonized by a small number of V. fischeri strains that can undergo significant genetic diversification, including by horizontal-gene transfer, over the course of ~1500 generations of growth in the organ. When the resulting population of symbionts is expelled into seawater, its genomic mix provides the genetic basis for selection during the subsequent environmental dispersal, and transmission to the next host.